Gender and ethnic features of Internet addiction among the student youth of Kyzyl and Krasnoyarsk - Yaskevich, Roman A.; Khamnagadaev, Igor I. (The New Research of Tuva, 2024)
The article analyzes the prevalence of various patterns of internet addictive behavior in a comparative aspect among students in Kyzyl and Krasnoyarsk. The study's conclusions are based on an analysis of the results of tests conducted on students from both cities. The survey was conducted through random sampling between September 2022 and May 2023, covering 993 participants of both genders who completed the Chen Internet Addiction Scale (CIAS) questionnaire, adapted by V. L. Malygin and K. A. Feklisov.A comparative analysis of the frequency and severity of different patterns of internet-addictive behaviors among groups differing in residence, ethnicity, and gender is presented. It was found that students in Kyzyl had a higher prevalence of more severe and persistent patterns of internet addiction compared to students in Krasnoyarsk, with 11.9% vs 7.9%, respectively. Special attention is paid to the issue of the influence of ethnicity on the development of Internet addiction among student youth in Kyzyl. The study found that ethnic characteristics are associated with a higher frequency of Internet addictive behavior, with Tuvan students in Kyzyl exhibiting a more pronounced and stable pattern than Russian students (12.4% vs 10.9%). Gender differences were also observed, with a higher incidence of Internet addiction among Tuvan girls (14.4%) compared to Tuvan boys (8.6%) and Russian girls (12.7%).
Keywords: student; Tuva; Kyzyl; Krasnoyarsk; Internet; Internet addiction; Tuvans; Russians